ASSESSMENT OF COMBINING ABILITY FOR YIELD AND YIELD RELATED TRAITS IN SPRING WHEAT (TRITICUM AESTIVUM L.) - RANA, US; FAROOQ, MO; ABBAS, W; NASIR, B; AHMAD, MS; IMTIAZ, M (Biological and Clinical Sciences Research Journal, 2024)
Grain yield and other related characters were studied in 18 F1 generations along with nine parents (six lines and three testers) which were evaluated for combining ability with three replications in a randomized complete block design (RCBD). The results indicated that among various lines, line 9479 was identified as a good general combiner for the traits, viz., spike length, spikelet’s per spike, and 1000-grain weight, whereas, Line 9486 appeared as a good general combiner for the characters, flag leaf area, plant height, peduncle length, number of tillers per plant and 1000-grain weight. Line 9515 for flag leaf area, plant height, and spike length. Line 9519 for the number of tillers per plant, grain yield per plant, and plant height; line 9520 for peduncle length, number of tillers per plant, grains per spike, grain yield per plant and 9521 was identified as good general combiner for the characters spike length, spikelet’s per spike, number of grains per spike and spike density. Tester Punjab-11 emerged as a good general combiner for the traits; peduncle length, plant height, flag leaf area, and number of tillers per plant, whereas, Tester Ass-11 appeared as a good combiner for the spike length, peduncle length, 1000-grain weight, and flag leaf area. Tester Chakwal-50 identified a good general combiner for the number of tillers per plant, plant height, grains per spike, spikelets per spike, grain yield per plant, 1000-grain weight, and spike density. Out of 18 cross combinations, seven crosses viz. 9479 × Aas-11, 9486 × Aas-11, 9515 × Aas-11, 9519 × Chakwal-50, 9520 × Punjab-11, 9521 × Punjab-11, and 9521 × Aas-11 emerged with significant positive SCA effects for grain yield per plant. Thus, these crosses can be exploited for grain yield per plant by using biparental mating system.